The reaction of the citizens of the Ukrainian SSR to the events of the Prague spring of 1968 (based on the documents of the branch state archive of the security service of Ukraine) - Руккас, Андрій; Лавренчук, Тимур (ВПЦ "Київський університет", 2025)
Background. The Prague Spring of 1968 was an attempt at political liberalization in Czechoslovakia that ended with a military invasion by the USSR and other Warsaw Pact countries, which the Kremlin justified as "international assistance." The Ukrainian leadership, particularly Petro Shelest, supported the intervention, although he also sought to preserve a certain degree of autonomy for the Ukrainian SSR. Party propaganda in the Ukrainian SSR actively justified the Soviet actions, but public sentiment was mixed: a significant part of the intelligentsia sympathized with Dubček's course, and among dissidents, a sense of solidarity with the Czechoslovak reformers grew. Despite the absence of mass protests, verbal forms of resistance were recorded, including listening to foreign radio broadcasts, informal correspondence, and radical acts of protest–most notably, the self-immolation of Vasyl Makukh. The Soviet authorities responded harshly to any signs of dissent: the KGB documented hundreds of cases of "anti-Soviet" expressions, confiscated leaflets, and punished activists. The events in Czechoslovakia became a catalyst for the politicization of Ukrainian society, the intensification of the human rights movement, and the expansion of dissident sentiment. Parallels with the suppression of the Hungarian uprising in 1956 confirmed that the Soviet system was prepared to act brutally to maintain control, but at the same time revealed deeper disillusionment within parts of society and the rise of oppositional attitudes – some of which have been documented thanks to the opening of KGB archives. Purpose. To analyze the reaction of the population of the Ukrainian SSR to the events of the 1968 Prague Spring based on recently declassified documents of the Ukrainian SSR Committee for State Security (KGB), with particular emphasis on regional differences in public sentiment.  Methods. The study employs a descriptive-analytical historical method to interpret archival documents, a comparative approach to contrast reactions across different regions, as well as oral history elements and content analysis to evaluate the nature of citizens' statements.  Results. The research found that public attitudes in the Ukrainian SSR in 1968 were ambivalent and far from monolithic. Significant regional discrepancies were revealed: while the western regions (in particular Transcarpathia and Lviv region) more frequently exhibited critical and antiregime evaluations of Soviet policy toward Czechoslovakia, the central and eastern regions tended to display loyal sentiments and support for the official line – although even there instances of anxiety and dissent were recorded. The Prague Spring acted as a catalyst for latent discontent: alongside open approval of the intervention, there coexisted critical judgments, fear of war, and sympathy for Czechoslovak reforms.  Conclusions. The KGB documents demonstrate that the official Soviet propaganda about "unanimous support" for the USSR's actions in Czechoslovakia did not reflect the real sentiments of a portion of the population. The people of the Ukrainian SSR reacted to the Prague Spring events with mixed feelings – from complete support to sharp condemnation. The security organs maintained strict control over public moods: they promptly recorded citizens' statements, identified "unreliable" individuals, and implemented preventive repressive measures. All this indicates the existence of hidden social tension in Soviet Ukraine and a divergence between the official ideology and citizens' genuine assessments.

Вступ. Празька весна 1968 р. стала спробою політичної лібералізації в Чехословаччині, що завершилася силовим вторгненням СРСР і країн Варшавського договору, яке Кремль обґрунтовував "інтернаціональною допомогою". Українське керівництво, зокрема Петро Шелест, підтримало інтервенцію, хоча водночас він прагнув зберегти певну автономію УРСР. Партійна пропаганда в УРСР активно виправдовувала дії СРСР, однак суспільні настрої були неоднозначними: значна частина інтелігенції симпатизувала курсу Дубчека, а серед дисидентів зростало відчуття солідарності із чехословацькими реформаторами. Попри відсутність масових протестів, фіксувалися вербальні форми спротиву, слухання іноземного радіо, неформальне листування, а також радикальні акти протесту, зокрема самоспалення Василя Макуха. Радянська влада жорстко реагувала на будь-які вияви незгоди: КДБ фіксував сотні випадків "антирадянських" висловлювань, вилучав листівки й карав активістів. Події в ЧССР стали поштовхом до політизації українського суспільства, активізації правозахисного руху та розширення дисидентських настроїв. Аналогії з придушенням угорського повстання 1956 р. підтвердили, що радянська система готова до жорстоких дій задля утримання контролю, але водночас виявили глибше розчарування частини суспільства та зростання опозиційних настроїв, які частково вдалося зафіксувати завдяки відкриттю архівів КДБ. Мета дослідження: проаналізувати реакцію населення Української РСР на події "Празької весни" 1968 р. на основі розсекречених документів Комітету державної безпеки (КДБ) УРСР, з особливим акцентом на регіональні відмінності суспільних настроїв.  Методи. Застосовано історичний описово-аналітичний метод для інтерпретації архівних документів, порівняльний підхід під час зіставлення реакцій у різних регіонах, а також методи усної історії та контент-аналізу для оцінювання характеру висловлювань громадян.  Результати. Встановлено, що суспільні настрої в УРСР у 1968 р. були амбівалентними й далеко не однорідними. Виявлено значні регіональні розбіжності: якщо в західних областях (зокрема на Закарпатті та Львівщині) частіше фіксувалися критичні й антирежимні оцінки радянської політики щодо Чехословаччини, то в центральних і східних областях переважали лояльні настрої й підтримка офіційної лінії, хоча і там траплялися вияви занепокоєння та незгоди. Простежено, що Празька весна стала каталізатором прихованого невдоволення: поряд із відкритим схваленням інтервенції існували критичні судження, страх перед війною та симпатії до чехословацьких реформ.  Висновки. Документи КДБ УРСР засвідчують, що офіційна радянська пропаганда про "одностайну підтримку" дій СРСР у Чехословаччині не відповідала реальним настроям частини населення. Населення УРСР реагувало на події Празької весни зі змішаними почуттями – від повної підтримки до різкого засудження. Органи держбезпеки здійснювали жорсткий контроль за настроями: оперативно фіксували висловлювання громадян, виявляли "нелояльних" осіб і вживали превентивних репресивних заходів. Усе це відображає існування в радянській Україні прихованого суспільного напруження і розбіжностей між офіційною ідеологією та реальними оцінками громадян.
Реагування громадян Української РСР на події "празької весни" 1968 року (за документами Галузевого державного архіву Служби безпеки України)
Keywords: Prague Spring; Ukrainian SSR; public opinion; social sentiments; KGB; Soviet propaganda; Czechoslovakia; Prague Spring; Ukrainian SSR; public opinion; social sentiments; KGB; Soviet propaganda; Czechoslovakia; Празька весна; 1968 рік; Українська РСР; громадська думка; суспільні настрої; КДБ; радянська пропаганда; Чехословаччина.; Празька весна; 1968 рік; Українська РСР; громадська думка; суспільні настрої; КДБ; радянська пропаганда; Чехословаччина